PENGARUH BRAND IMAGE, WORD OF MOUTH, DAN PERCEIVED VALUE TERHADAP KEPUTUSAN PEMBELIAN STUDI KASUS PADA SEPEDA MERK POLYGON DI KABUPATEN PONOROGO - Sasmita, Satria; Wijayanto, Heri; Hartono, Sri (Bussman Journal : Indonesian Journal of Business and Management, 2022)
This study aims to determine the effect of Brand Image, Word of Mouth and Perceived Value on Polygon Bike Purchase Decisions in Ponorogo. The method used in this study is a quantitative method. The data from this study were obtained through distributing questionnaires with written statements to respondents and analyzed using the SPSS 25 software application. The population in this study was the bicycle community in Ponorogo. The sample in Tian's research amounted to 100 using the Simple Random Sampling technique. The results of this study indicate that: (1) There is an influence between Brand Image on the decision of Polygon bicycles in Ponorogo. (2) There is an influence between Word of Mouth on the decision to purchase a Polygon bicycle in Ponorogo (3) There is an influence between Perceived Value on the decision to purchase a Polygon bicycle in Ponorogo. (4) There is an influence between Brand Image, Word Of Mouth and Perceived Value on the decision to purchase Polygon bicycles in Ponorogo